Combination of Leunca Herb Ethanolic Extract and Doxorubicin Suppresses HeLa Cellsâ Growth - Sarmoko, .; Putri, Dyaningtyas D. P.; Puspitasari, Endah; Anindyajati, .; Meiyanto, Edy (Indonesian Journal of Cancer Chemoprevention, 2011)
Leunca (Solanum nigrum L.)ethanolic extractshowedcytotoxic activity on several cancer cell lines (HepG2, HT-29) and showed anti-proliferative activityon MCF-7 cells. Its application as a combinationagent in chemotherapy will increase the effectivity and reduce the toxicity of chemotherapy. We predict that application of combinatorial chemotherapy in cancer treatment will be more effective and less toxic compared to single treatment. Our research aims to investigate the cytotoxic activitiy of leunca herbs ethanolic extract alone and in combination with doxorubicin on HeLa cell line. MTT assay was conducted to measure the growth inhibitory effect of leunca herbs ethanolic extract and combinatorial treatments. Leunca herb ethanolic extract (5, 50, 250 μg/ml) increased the cytotoxic effect of doxorubicin compared to doxorubicin alone. The strongest cytotoxic activity resulted from the combination of 250 μg/ml leunca herbs ethanolic extract and 250 nM doxorubicin. Based on our results, leunca herbs ethanolic extract is a potential chemopreventive agent, while its molecular mechanism needs to be explored.Keyword : Leunca herbs ethanolic extract, doxorubicin, HeLa, MTT assay